Eksplorasi Kualitatif Pengambilan Keputusan Individu Dan Perilaku Organisasi - Eltama, Naura Firyal; Saputri, Nisa Aulia Budi; Fatimah, Andien Rezahra Ayu; Mu’az, Khadlan; Ramadhani, Didhiet; Sari, Dinda Erliana; Julianto, Reza; Sunarti, Sunarti (EL-EMIR Institute, 2024)
This research aims to explore individual decision-making processes and organizational behavior, as well as understand the factors that influence these two aspects in an organizational context. Individual decision making is the process of selecting the best alternative from various existing options, while organizational behavior includes the interaction patterns and actions of organizational members in achieving common goals. The research method used is a qualitative method, involving in-depth interviews, participant observation, and narrative analysis. This research was conducted in several organizations with various structures and cultures, to get a comprehensive picture of how decisions are made and how organizational behavior is formed. The results show that individual decision making is influenced by a combination of rational and emotional factors, including cognitive biases, risk perception, and social pressure. In addition, organizational behavior is strongly influenced by organizational culture, hierarchical structure, and group dynamics. Factors such as communication, motivation, and leadership play an important role in influencing the behavior of organizational members. This research confirms the importance of a deep understanding of the decision-making process and organizational behavior to increase effectiveness and efficiency in achieving organizational goals. The results of this research can be a practical guide for organizational leaders in managing and leading their organizations better.